The modernization practices of pesantrens in Salatiga - Fani Farida (IAIN Salatiga, 2017)
This study aims to analyze the practices of modernization in the pesantren of Salatiga in 2017. Modernization of Islamic boarding schools (pesantren) should be developed in order that their function as an Islamic educational institution is not eroded by times. In this study, the authors used a qualitative descriptive research method by conducting interviews, observation and field studies to three boarding school in Salatiga namely Pondok Pesantren An Nida, Pondok Pesantren Al Falah, and Pondok Pesantren Sunan Giri. The results of this study stated that the practices of modernization among others modernization of the curriculum; dynamic punishment; as well as the utilization of information technology and transformation to support boarding activities. Whereas the causes of modernization internal factors: curriculum of schools undergoing change, free use of communication tools, permissibility of carrying transportation, as well as a dynamic punishment; external factors (the interaction of students with the environment outside of pesantren and build a network with outsiders). The impact of modernization on the existence of pesantren include positive impacts for boarding schools (pesantren become more widely known and the curriculum becomes more advanced), for students (make students knowledgeable, students more familiar with the technology, the mobility of students becomes easier, and students become more self through self-employment. the negative effects tend to students who then impact the schools, such as students tend to be individualized; students more easily break the rules boarding school, and the erosion of moral values of students.